2005
DOI: 10.1002/bdd.446
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence evaluation of two brands of meloxicam tablets (promotion® and mobicox®): pharmacokinetics in a healthy female Mexican population

Abstract: We conducted a randomized, crossover study in 23 healthy young female volunteers to compare the bioavailability of two brands of meloxicam (7.5 mg) tablets and to obtain pharmacokinetic parameters of this molecule in Mexican population not reported previously. Two tablets (15 mg) were administered as a single dose on 2 treatment days separated by a 1-week washout period. After dosing, serial blood samples were collected for a period of 72 h. Plasma harvested was analyzed for meloxicam by a modified and validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…When considering the study performed by Marcelín-Jiménez et al35 in a Mexican female population, although the T max value was similar to that estimated in the present study, both C max and AUC 0–24 values were found to be higher. However, differences in sex, body weight, genetic profile, and pharmaceutical composition of tablets are likely to explain the differences between the Italian and Mexican studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When considering the study performed by Marcelín-Jiménez et al35 in a Mexican female population, although the T max value was similar to that estimated in the present study, both C max and AUC 0–24 values were found to be higher. However, differences in sex, body weight, genetic profile, and pharmaceutical composition of tablets are likely to explain the differences between the Italian and Mexican studies.…”
Section: Discussionsupporting
confidence: 86%
“…However, the main study objective was not to investigate the complete PK profiles of meloxicam in healthy volunteers, since this information has been previously provided by other authors,19–22,34,35 but rather to compare PK and PD patterns between branded and generic meloxicam. On this basis, we performed a blood-sampling collection during the dissolution, absorption, and distribution PK phases, assuming that the elimination phase would not be significantly affected by the pharmaceutical formulation.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC 0-∞ of meloxicam in Chinese HVs in the fasting arm was 59 042 ng • h/mL, similar to that in Egyptian 21 and Mexican 22 HVs following a single dose of 15 mg (64 400 and 62 730 ng • h/mL, respectively), and 1.9 to 2.1 times higher than that in German 23 and Pakistani 24 HVs (31 846 and 28 700 ng • h/mL, respectively). The average C max of meloxicam in Chinese HVs was 1939 ng/mL, which was similar to that in Egyptian and Mexican volunteers (1800 and 2291 ng/mL, respectively), and 1.8 times higher than that in German and Pakistani volunteers (1065 and 1100 ng/mL, respectively).…”
Section: Discussionsupporting
confidence: 54%
“…This sample size was based on within subject standard deviation for the log AUC known from previously published studies and on the bioequivalence criterion (90% confidence that the estimated population mean ratio lies between 80% and 125%). 2,5,6,8,9…”
Section: Study Participantsmentioning
confidence: 99%
“…It is well absorbed after oral administration with an absolute bioavailability of 89%. [4][5][6] Meloxicam reaches maximum plasma concentration (C max ) at 9-11 h after a 30 mg dose and at 2.5 to 7 h after a 15 mg dose. The mean volume of distribution is approximately 10 L. It is ~99.4% bound to plasma proteins within the therapeutic dose range.…”
Section: Introductionmentioning
confidence: 99%